Psychotherapy research for compulsive buying-shopping disorder: Quo vadis? - Astrid Müller; Patrick Trotzke; Patricia Schaar; Tobias A. Thomas; Ekaterini Georgiadou; Sabine Steins-Loeber (Addictive Behaviors Reports)
Aim The aim of this position paper is to address the question of how psychotherapy research for compulsive buying-shopping disorder (CBSD) should develop further. Method: After a brief summary of existing psychotherapy research, this paper concentrates on the advantages and shortcomings of previous psychotherapy studies and offers recommendations for future psychotherapy research in the domain of CBSD. Results: Systematic reviews indicate that cognitive behavioural therapy is the most researched form of psychotherapy and presents a helpful intervention for reducing the symptom severity of CBSD. Notwithstanding the positive outcomes, the psychotherapy studies to date are limited by methodological shortcomings, which reduce their validity and generalizability. While research into the psychological mechanisms of offline and online CBSD has expanded considerably, psychotherapy research has not kept pace with this growth. Although the majority of individuals with CBSD engage in online shopping, the problematic usage of shopping websites has not been considered in any of the treatment studies to date. Conclusion: The application of the experimental medicine framework to psychotherapy research for CBSD may enhance the integration of findings on psychological mechanisms of CBSD with existing treatment concepts for CBSD. Moreover, it is necessary to consider the impact of technological factors and e-marketing in the context of treatment. There is a need for 1) proof-of-concept studies to test specific interventions that target specific psychological processes and mechanisms of CBSD, and 2) high-quality psychotherapy studies to test the efficacy and effectiveness of new treatment approaches in accordance with the scientific standards for randomised controlled trials